Abiotic Factors Affecting Seed Germination and Early Seedling Emergence of Large Crabgrass (Digitaria sanguinalis) - WANG,Y.H. (2018)
ABSTRACT: Large crabgrass is one of the worst exotic weed in tropical, subtropical, and temperate regions of the world. In this study, the abiotic factors affecting seed germination and early seedling emergence of large crabgrass were investigated under laboratory conditions. The optimum temperatures of germination occurred at the range from 25 to 35 oC under 12 h light/12 h dark condition. Some seeds could germinate in the dark, but light exposure significantly stimulated the germination. Large crabgrass seed was tolerant to salinity level range of 0 to 160 and low water potential (11% germination at -0.8 MPa). Medium pH had no significant effect on seed germination and more than 90% seeds germination was obtained over a broad pH range from 4.0 to 10.0. Seed germination was significantly influenced by heat-shock and completely inhibited at 140 oC for 5 min. The greatest seedling emergence rate was 96% when seeds were planted at a soil depth of 1 cm. Knowledge of germination biology obtained from this study will be useful in the development of the integrated weed management strategies for this species, and to avoid its establishment as a troublesome weed in economically important cropping regions.